Pengaruh Social Media Marketing Instagram Terhadap Keputusan Pembelian Ulang Produk Scarlett Whitening - Afina, Alya; Widarmanti, Tri (Rifa'Institute, 2022)
Marketing activities using social media are widely used by business actors to introduce or promote goods and services. Indonesia is one of the countries with the most Instagram social media users in 2021 with a total of 93 million users, Scarlett Whitening is a local skincare brand owned by an Indonesian artist that was founded in 2017. The sale of this product is only done online through Instagram as a promotional tool. This study aims to determine the influence of social media marketing on Instagram on value equity, brand equity, relationship equity, and repurchase. This research uses descriptive quantitative with Structural Equation Modeling (SEM) which is analyzed using SmartPLS 3.0 and SPSS software to process the data. The results showed that the social media marketing activity had a positive and significant effect on value equity, brand equity, and relationship equity. Also, brand equity and relationship equity had a positive and significant effect on repurchase decisions. While value equity has no effect on repurchase decisions. The effect of social media marketing activities is significant on value equity, brand equity and relationship equity. While Value equity has no effect on repurchase decisions, Brand equity and relationship equity also have a positive and significant effect on repurchase decisions.